Association between Life's Crucial 9 and Cardiorenal syndrome: the mediating role of weight-adjusted-waist index - Fu, Huanjie; Liu, Zhichao; Yu, Hao; Zhao, Yisheng; Gan, Yongkang; Chen, Jinhong; Liu, Eryue (Frontiers in Nutrition, 2025)
BackgroundRecent studies have indicated a link between cardiovascular wellbeing, obesity, and Cardiorenal syndrome (CRS). The impact of excessive body mass on the dynamics between heart health and CRS remains unclear. Life's Crucial 9 (LC9) serves as an innovative parameter for cardiac evaluation, whereas the Weight-Adjusted Waist Index (WWI) offers a nuanced metric for gauging obesity. This investigation explores the association between LC9 and CRS, and examines WWI's potential moderating influence.MethodsData from the National Health and Nutrition Examination Survey (NHANES) was employed. Subgroup analyses were conducted, restricted cubic spline (RCS) modeling was utilized, and multivariate logistic regression was performed to assess the relationship between LC9 and CRS. Furthermore, we conducted a mediation analysis to investigate the influence of WWI on this relationship.ResultsThe cohort consisted of 25,379 participants, with 1,172 diagnosed with CRS. In the adjusted logistic regression model, an increase of ten points in LC9 correlated with a 25% reduction in CRS risk (OR = 0.75, 95% CI: 0.68, 0.82). Each incremental unit in WWI corresponded to a 63% increase in the risk of CRS (OR = 1.63, 95% CI: 1.46, 1.83). Tertile analysis of LC9 and WWI demonstrated consistent patterns, with significant p-values for trends < 0.001. RCS modeling confirmed a significant inverse linear correlation between LC9 and CRS (overall p < 0.001; non-linear p = 0.307) and a direct linear relationship between WWI and CRS (overall p < 0.001; non-linear p = 0.814). Mediation analysis revealed that WWI mediated 24.47% of the effect of LC9 on CRS (p < 0.001).ConclusionThe findings indicate a strong inverse relationship between LC9 and CRS, with WWI serving as a partial mediator in this interaction. The findings emphasize the intricate interactions between LC9 and CRS, illustrating the essential function of WWI as a mediator in future research endeavors.